English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

3 answers

r=lnR0/Tc
r*Tc = lnR0
e^(r*Tc) = e^(lnR0)
e^(r*Tc) = R0

That's assuming you mean ln(R0)/Tc, and not ln(R0/Tc)

2007-06-12 13:37:57 · answer #1 · answered by McFate 7 · 0 0

if it's r = ln(R0/Tc) then:
e^r = R0/Tc

if it's r = ln(R0)/Tc, then:
e^(r*Tc) = R0

2007-06-12 20:38:13 · answer #2 · answered by Crystal 2 · 0 0

r = ln (Ro/Tc)
exp(r) = exp(ln (Ro/Tc))
e^r = Ro/Tc
Ro = Tc * e^r: e = 2.718281828...

2007-06-12 20:38:03 · answer #3 · answered by telsaar 4 · 0 0

fedest.com, questions and answers